MULTIPLE DURAL ARTERIOVENOUS MALFORMATIONS - CHIEWVIT, Pipat; CHAWALPARIT, Orasa; CHUROJ, Anchalee; SUTHIPONGCHAI, Suthisak; Sup CHOI, In (The ASEAN Journal of Radiology, 2023)
Four cases of multiple dural arteriovenous malformations (DAVMs) including base of skull are reported. Two of them have a DAVMs involving the cavernous sinus and separate AVMs in base of skull. The third patient has the symptomatic DAVMs involving straight sinus and the last patient has DAVMs involving torcular and both also have the second DAVMs involving superior sagittal sinus. All of the second DAVMs are incidentally detected by cerebral angiography. Reviewing of previous reports of this occurrence and the vascular anomalies that can association with dural AVMs are dis- cussed.